The physical and mechanical properties of potato (Solanum tuberosum L.) tubers as related to the automatic separation from clods and stones - Ghasem Abedi; Shamsollah Abdollahpour; Mohammad Reza Bakhtiari (Research in Agricultural Engineering, 2019)
In the current research, some of the mechanical and physical properties of two industrial varieties of potato tubers that have a prominent role in the mechanised separation process from clods and stones were investigated. These properties include the physical dimension, mass, volume, sphericity, surface area, density, projected areas and Young's modulus. In addition, the static coefficient of friction and rolling resistance for tubers on five surface materials were determined. The tuber's size positively affected the physical and mechanical properties of the tubers. The frictional properties of the tubers were affected by the tuber size, the surface type, and the interaction between them. The results showed that most of the apparent properties for the Sante variety were greater than those of the Marfona variety. The static coefficient of friction for the tubers on a wood surface was the maximum and was the minimum value on a galvanized sheet, but for the tuber's rolling resistance, the results were inversed. The results proposed that the automatic separation of the potato tubers from the impurities using the properties of the crop is possible.